Tingkat Kemampuan Penyusunan RPPH Calon Guru PAUD di Era Kurikulum Merdeka Belajar - Anggara Dwinata; Sayid Marifatulloh; Emy Yunita Rahma Pratiwi; Fannidya Hamdani Zeho; Samsiah Samsiah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
The role of the independent learning curriculum influences the level of early childhood education institutions. This institution has the responsibility to actualize the preparation of daily learning implementation plans as a form of guidance in carrying out the learning process every day. The format for compiling RPPH consists of program identity, materials, tools and materials, learning resources, series of activities, learning models, and assessments. The research method used is a quantitative study with a survey research design. The research sample was ten students of the Early Childhood Education Study Program who had prepared RPPH according to the location of the school they worked at. Data analysis techniques using percentages and statements. Based on the results of the study, the average survey level obtained results of 91% with a very good predicate. RPPH is classified as very good, categorized as RPPH that is relevant to be applied in early childhood education institutions to be able to maximize its potential to teach preschool children.